Genetic polymorphism of the adenosine A₂A receptor is associated with habitual caffeine consumption - Cornelis, Marilyn C; El-Sohemy, Ahmed; Campos, Hannia (The American journal of clinical nutrition, 2007)
BACKGROUND: Caffeine is the most widely consumed stimulant in the world, and individual differences in response to its stimulating effects may explain some of the variability in caffeine consumption within a population. OBJECTIVE: We examined whether genetic variability in caffeine metabolism [cytochrome P450 1A2 (CYP1A2) -163A[rightward arrow]C] or the main target of caffeine action in the nervous system [adenosine A₂A receptor (ADORA2A) 1083C[rightward arrow]T] is associated with habitual caffeine consumption. DESIGN: Subjects (n = 2735) were participants from a study of gene-diet interactions and risk of myocardial infarction who did not have a history of hypertension. Genotype frequencies were examined among persons who were categorized according to their self-reported daily caffeine intake, as assessed with a validated food-frequency questionnaire. RESULTS: The ADORA2A, but not the CYP1A2, genotype was associated with different amounts of caffeine intake. Compared with persons consuming <100 mg caffeine/d, the odds ratios for having the ADORA2A TT genotype were 0.74 (95% CI: 0.53, 1.03), 0.63 (95% CI: 0.48, 0.83), and 0.57 (95% CI: 0.42, 0.77) for those consuming 100-200, >200-400, and >400 mg caffeine/d, respectively. The association was more pronounced among current smokers than among nonsmokers (P for interaction = 0.07). Persons with the ADORA2A TT genotype also were significantly more likely to consume less caffeine (ie, <100 mg/d) than were carriers of the C allele [P = 0.011 (nonsmokers), P = 0.008 (smokers)]. CONCLUSION: Our findings show that the probability of having the ADORA2A 1083TT genotype decreases as habitual caffeine consumption increases. This observation provides a biologic basis for caffeine consumption behavior and suggests that persons with this genotype may be less vulnerable to caffeine dependence.